Analisis Dan Usulan Implementasi Konsep 5s (Seiri, Seiton, Seiso, Seiketsu, Dan Shitsuke) Di Praktek Ahli Gigi - Nur Ramadhan; Apid Hapid Maksum (Jurnal Ilmiah Wahana Pendidikan, 2022)
In the age of globalization, industrial competition is so tough, industry is vying for the best, which is not only what is happening to the company but almost totally experiencing the competition. Dental ihon is a service - centered workplace, especially dental health. The dental iyon consists of competence such as the installing of false teeth, braces, dental braces, and so forth. As for the approach done is with the kaizen method. Kaizen includes a repair understanding one of which is 5s (seiri, seitone, seiso, seiso, seiketsu, shitsuke) 5s in English is also called 5r (concise, neat, resik, rawat, industrious). The result of the 5s application at dental workplace, there are several problems found in the workplace. Conditions in the unorganized workplace made the workplace irregular. Problems found in the workplace can be seen at table 4.3. The work environment evaluations prior to the application of the 5s program 5s are simple improv programs at the workplace that could be implemented immediately. Table 4.4 shows 5s assessments in the workplace before applying the 5s concept.